2022
DOI: 10.1097/gox.0000000000004112
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Breast Reconstruction is Associated with Lower 90-day Readmission Rates

Abstract: Background: Breast reconstruction is associated with improved quality of life after mastectomy. Options for breast reconstruction include autologous and implant-based methods. Although autologous reconstruction is more technically challenging and requires longer operative time, it is thought of as the gold standard. Our study examined differences in 90-day readmission rates between implant-based and autologous breast reconstruction using discharge data from the National Readmission Database, Healthcare Cost an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Literature is inconclusive regarding the impact of reconstructive type on readmission rates. A recent study using the National Readmission Database found that patients undergoing AR were 23% less likely to be readmitted within 90 days after discharge than those who underwent IBR, whereas another metaanalysis reported comparable risks of unplanned HR 13,14) . This incongruence suggests that patient comorbidities, surgical techniques, and postoperative care may have a higher impact on readmission rates than procedure type.…”
Section: Discussionmentioning
confidence: 99%
“…Literature is inconclusive regarding the impact of reconstructive type on readmission rates. A recent study using the National Readmission Database found that patients undergoing AR were 23% less likely to be readmitted within 90 days after discharge than those who underwent IBR, whereas another metaanalysis reported comparable risks of unplanned HR 13,14) . This incongruence suggests that patient comorbidities, surgical techniques, and postoperative care may have a higher impact on readmission rates than procedure type.…”
Section: Discussionmentioning
confidence: 99%
“…16 Other studies have corroborated these findings, with approximately 40% of patients undergoing mastectomy, the rate of risk-reducing bilateral mastectomies increasing, and increased rates of PMR. 17–20…”
Section: Discussionmentioning
confidence: 99%
“…16 Other studies have corroborated these findings, with approximately 40% of patients undergoing mastectomy, the rate of risk-reducing bilateral mastectomies increasing, and increased rates of PMR. [17][18][19][20] Among the augmented patients, 80% underwent PMR. This was significantly higher than 49.9% of the nonaugmented group and demonstrates that patients who have undergone previous augmentation mammaplasty may be more likely to be interested in, or be able to undergo, postmastectomy breast reconstruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The superior aesthetic outcome is mirrored by higher rates of overall patient-reported satisfaction when compared with implants. 1,2 In addition to technical advances in donor site selection, which have broadened the range of body types reconstructive surgeons can care for, changes in legislature have eroded substantial cost barriers, allowing more women to pursue life-changing treatment. 3 Despite the efforts of public health policymakers, the steady rise in reconstruction rates has not been proportional across races, begetting an unfortunate disparity.…”
Section: Introductionmentioning
confidence: 99%